Infant feeding - Cross, Wilma Greene (My University, 1904)
Introduction: Surely no one who breathes the air of liberty-loving America, who enjoys the protection of its just laws, and who partakes of the benefits of it's worthy institutions can fail to have it's interests uppermost in every activity of his life. No one who names himself an “American” can disconnect his duties to his country with those of his religion. Yet very frequently through ignorance or unconcern, individuals do not realize what is the basis of their nation's welfare. Laws are enacted in the attempt to diminish wrong doing and institutions are established for the purpose of confining those who are abnormal. But these means prove ineffectual for the root of the evil has not been reached. The diseases of crimnality and imbecility, which are at once the disgrace and bane of this country, can not be cured by legislative enactments nor appropriations. The chief responsibility must unquestionably rest upon the home and more specifically upon the food consumed by the family. It would be narrow to assert that the latter has the sole influence in moulding the character of the individual and subsequently of the state but that it is of paramount importance is made certain both by the history of individuals and of nations. That the excessive consumption of animal food tends greatly to stimulate nervous activity is evidenced by the Englishing-speaking peoples who are the greatest users of animal food and at the same time the most energetic and the most pugnacious race on the globe. In contrast the uniformly non-aggressive and sluggish tendency of the Orientals whose diet is mostly farinaceous, offers convincining proof of the fact that such a dietary has a non-stimulating effect. Whether the results of these diets are due to their poorly balanced nutritive ratio or to some property peculiar to the animal and vegetable foods respectively, is of little moment here. It is sufficient…
Citation: Cross, Wilma Greene. Infant feeding. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Food; Eating Right; Nutrition; Infant Diet; Theses